A meta-analysis for neurobehavioural effects due to electromagnetic field exposure emitted by GSM mobile phones. Issue 5 (10th October 2007) - Barth, A; Winker, R; Ponocny-Seliger, E; Mayrhofer, W; Ponocny, I; Sauter, C; Vana, N
Abstract : Background and objective: Numerous studies have investigated the potential effects of electromagnetic fields (EMFs) emitted by GSM mobile phones (∼900 MHz to ∼1800 MHz) on cognitive functioning, but results have been equivocal. In order to try and clarify this issue, the current study carried out a meta-analysis on 19 experimental studies. Design: Meta-analysis. Methods: Nineteen studies were taken into consideration. Ten of them were included in the meta-analysis as they fulfilled several minimum requirements; for example, single-blind or double-blind experimental study design and documentation of means and standard deviation of the dependent variables. The meta-analysis compared exposed with non-exposed subjects assuming that there is a common population effect so that one single effect size could be calculated. When homogeneity for single effect sizes was not given, an own population effect for each study and a distribution of population effects was assumed. Results: Attention measured by the subtraction task seems to be affected in regard to decreased reaction time. Working memory measured by the N-back test seems to be affected too: under condition 0-back target response time is lower under exposure, while under condition 2-back target response time increases. The number of errors under condition 2-back non-targets appears to be higher under exposure. Conclusion: Results of the meta-analysis suggest that EMFs may have a small impact on human attention and working memory.